2012
DOI: 10.3748/wjg.v18.i4.383
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism withinErbB4is associated with risk for hepatocellular carcinoma in Chinese population

Abstract: rs6147150 may be associated with HCC risk, in part through let-7c-mediated regulation, and may be involved in the pathogenesis of HCC in Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…The genotype distributions for GSTM1 genetic polymorphisms in control subjects were inconsistent with the results of previous studies in Chinese population (Chiyomaru et al, 2011;Yu et al, 2011;Jiang et al, 2012;Senthilkumar Thirumurugan, 2012;Xu et al, 2013;Li et al, 2012Li et al, , 2015b. The frequency of the GSTM1 null genotype was 32.83%, which is similar to the genotype frequencies observed in Asian population and African American populations (about 30%), but is different from that in Caucasians (about 50%).…”
Section: Discussioncontrasting
confidence: 38%
“…The genotype distributions for GSTM1 genetic polymorphisms in control subjects were inconsistent with the results of previous studies in Chinese population (Chiyomaru et al, 2011;Yu et al, 2011;Jiang et al, 2012;Senthilkumar Thirumurugan, 2012;Xu et al, 2013;Li et al, 2012Li et al, , 2015b. The frequency of the GSTM1 null genotype was 32.83%, which is similar to the genotype frequencies observed in Asian population and African American populations (about 30%), but is different from that in Caucasians (about 50%).…”
Section: Discussioncontrasting
confidence: 38%
“…According to the inclusion criteria, 14 case-control studies (Gao et al, 2009;Chen et al, 2010;Qi et al, 2010;Akkiz et al, 2011a,b,c;Xu et al, 2008Xu et al, , 2011bLiu et al, 2012b;Xiang et al, 2012;Yu et al, 2012;Zhang et al, 2011Zhang et al, , 2012Zhou et al, 2012) were included in this meta-analysis and 134 were excluded. The flow chart of the study selection process is shown in Figure 1.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…However, this meta-analysis not performed a sub-group study in Chinese population. Yu et al (2011) conducted a meta-analysis in Chinese and included 16 studies for the relationship between GSTT1 gene polymorphism and HCC risk in Chinese, and they found that the null genotypes of GSTT1 was associated with increased risk of HCC. The number of included studies in our meta-analysis was larger than the previous meta-analyses.…”
Section: Discussionmentioning
confidence: 99%